Assessment of precipitate formation on interaction of irrigants used in different combinations: An in vitro study - Amarnath Shenoy; Nagesh Bolla; Sayish; Raj K Sarath; C H Sunil Ram; Sumlatha (Wolters Kluwer Medknow Publications, 2013)
Introduction: Irrigants play an essential role in the successful debridement and disinfection of pulp space. Various combination of irrigants used during root canal treatment enhance their efficacy, but some form precipitates which affects the diffusion of intracanal medicaments and the seal of the obturated root canal. Aim: To evaluate the combination of various irrigants whether it forms the precipitate and also to quantify the amount of precipitate formed. Materials and Methods: Five different irrigants were taken in ten test tubes each having the combination of two irrigants and observed for 2 min for precipitate formation. Results: One-way-ANOVA test revealed more amounts of precipitate with 2% Chlorhexidine (CHX) 5% Tulsi followed by 2% CHX, 5% Neem and 3% Sodium hypochlorite 2% CHX. Conclusion: Precipitate formation is seen more with the 2% CHX-5% Neem followed by 2% CHX-5% Tulsi when compared with the control group. When these combinations of irrigants were used, intermediate flushes of saline or distilled water reduced the amount of precipitate.